Crystalline silicon PV module degradation after 20 years of field exposure studied by electrical tests, electroluminescence, and LBIC. (17th November 2015) - Pozza, Alberto; Sample, Tony
Abstract: Standardized tests to assure the reliability of photovoltaic modules and to detect possible early failures of modules when exposed in the field, due to design flaws or to the use of non‐appropriate materials, have played an important role in the successful growth of photovoltaic market in recent years. In order for this growth to be sustainable in coming years, it is crucial to keep the confidence of investors in standard well‐established technologies and to increase confidence in new emerging technologies. For these reasons, there is an ongoing work for the improvement of current tests and for the development of new ones, which besides assuring module reliability in the field, have also the aim of predicting their lifetime. The analysis of degradation of modules that were field exposed over a long period of time is fundamental to identify the degradation mechanisms and to collect statistics on modules behavior. This work focuses on the analysis of the change of the photovoltaic module electrical characteristics after approximately 20 years of field exposure, considering differences in the design of cells that were used for the production of these modules, which were identified by detailed visual inspection. Failure modes were investigated by comprehensive visual inspection and the use of spatially resolved analysis techniques as follows: laser beam‐induced current and electroluminescence. The main failure mode identified was yellowing of the encapsulant. © 2015 The Authors. Progress in Photovoltaics: Research and Applications published by John Wiley & Sons Ltd. Abstract : Crystalline silicon modules that were field exposed for 20 years and that could be divided into three groups according to the layout of the front‐side metallization grid of cells used for their production were analyzed in detail with electrical characterization, electroluminescence, and laser beam‐induced current. The degradation rate was on average 0.22% / year for Pmax, but significant differences between the different groups were highlighted, stressing the importance of avoiding variations in the manufacturing process and in the materials used for production.